EAACI Guidelines on Allergen Immunotherapy: Allergic rhinoconjunctivitis. Issue 4 (30th October 2017) - Roberts, G.; Pfaar, O.; Akdis, C. A.; Ansotegui, I. J.; Durham, S. R.; Gerth van Wijk, R.; Halken, S.; Larenas‐Linnemann, D.; Pawankar, R.; Pitsios, C.; Sheikh, A.; Worm, M.; et al.
Abstract: Allergic rhinoconjunctivitis (AR) is an allergic disorder of the nose and eyes affecting about a fifth of the general population. Symptoms of AR can be controlled with allergen avoidance measures and pharmacotherapy. However, many patients continue to have ongoing symptoms and an impaired quality of life; pharmacotherapy may also induce some side‐effects. Allergen immunotherapy (AIT) represents the only currently available treatment that targets the underlying pathophysiology, and it may have a disease‐modifying effect. Either the subcutaneous (SCIT) or sublingual (SLIT) routes may be used. This Guideline has been prepared by the European Academy of Allergy and Clinical Immunology's (EAACI) Taskforce on AIT for AR and is part of the EAACI presidential project "EAACI Guidelines on Allergen Immunotherapy." It aims to provide evidence‐based clinical recommendations and has been informed by a formal systematic review and meta‐analysis. Its generation has followed the Appraisal of Guidelines for Research and Evaluation (AGREE II) approach. The process included involvement of the full range of stakeholders. In general, broad evidence for the clinical efficacy of AIT for AR exists but a product‐specific evaluation of evidence is recommended. In general, SCIT and SLIT are recommended for both seasonal and perennial AR for its short‐term benefit. The strongest evidence for long‐term benefit is documented for grass AIT (especially for the grass tablets) where long‐term benefit is seen. To achieve long‐term efficacy, it is recommended that a minimum of 3 years of therapy is used. Many gaps in the evidence base exist, particularly around long‐term benefit and use in children. Abstract :